1991
DOI: 10.1055/s-0038-1648199
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Thrombomodulin Antigen in Conditioned Medium Is Increased by Damage of Endothelial Cells

Abstract: SummaryThrombomodulin (TM) exists not only in endothelial cells but also in circulating plasma as soluble heterogeneous fragments. A release mechanism of soluble TM antigen from endothelial cells was investigated. Cultured human umbilical vein endothelial cells released about 0.6% of total cellular TM antigen into conditioned medium during 24 h. The release of TM antigen was not influenced by addition of various concentrations (0.01-5.0 μM) of monensin, which inhibits intracellular transport of secretory prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
197
3
6

Year Published

1992
1992
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(211 citation statements)
references
References 24 publications
5
197
3
6
Order By: Relevance
“…They suggested that the pathophysiology of neuropathy might not be due to systemic vasculitis, but rather to microvasculitis, causing ischemia in the vasa nervorum around peripheral nerves. Thrombomodulinis thought to be a good indicator of vascular injury (9,10). In this case, elevated levels of platelet and thrombomodulin before treatment with PSLwere also found.…”
Section: Discussionsupporting
confidence: 53%
“…They suggested that the pathophysiology of neuropathy might not be due to systemic vasculitis, but rather to microvasculitis, causing ischemia in the vasa nervorum around peripheral nerves. Thrombomodulinis thought to be a good indicator of vascular injury (9,10). In this case, elevated levels of platelet and thrombomodulin before treatment with PSLwere also found.…”
Section: Discussionsupporting
confidence: 53%
“…TM is a high-affinity thrombin receptor on the surface of vascular endothelial cells and a cofactor in the activation of protein C. 23 There is a good correlation between TM levels and clinical complications related to endothelial cell injury in septicemia, VOD and GVHD. 16 Increased TM levels in patients with BMT-TMA have been reported by Zeigler et al 15 They tested a ratio of TM:creatinine to provide a measure of the renal contribution to the TM elevation.…”
Section: Discussionmentioning
confidence: 99%
“…vWF was measured as described previously (28,29). Serum TM was determined by a one-step sandwich enzyme immunoassay, the reported sensitivity of which is 1 mg/l for soluble TM (30,31). Total cholesterol, triglyceride and high-density lipoprotein (HDL)-cholesterol were determined using an autoanalyzer.…”
Section: Serum Parametersmentioning
confidence: 99%